Clinical neurologic indices of toxicity in animals. - O'Donoghue, J L (1996)
The fundamental structures and functions of the nervous systems of animals and humans are conserved in many ways across species. These similarities provide a basis for developing common neurologic examinations for a number of species of animals and also provide a basis for developing risk assessments across species for neurologic end points. The neurologic examination requires no expensive equipment and can be conducted in the field or wherever impaired animals are identified. The proper conduct of neurologic examinations in animals assumes that the examiner has a fundamental understanding of the normal structure and function of the nervous system as well as knowledge about the spontaneous disease background of the species being studied.